Rating the seriousness of maternal and child health outcomes linked with pregnancy weight gain - Bodnar, Lisa M. (Paediatr Perinat Epidemiol, 2020)
BACKGROUND: Current pregnancy weight gain guidelines were developed based on implicit assumptions of a small group of experts about the relative seriousness of adverse health outcomes. Therefore, they will not necessarily reflect the values of women. OBJECTIVE: To estimate the seriousness of 11 maternal and child health outcomes that have been consistently associated with pregnancy weight gain by engaging patients and health professionals. METHODS: We collected data using an online panel approach with a modified-Delphi structure. We selected a purposeful sample of maternal and child health professionals (n=84) and women who were pregnant or recently postpartum (patients) (n=82) in the U.S. as panelists. We conducted 3 concurrent panels: professionals only, patients only, and patients and professionals. During a 3-round online modified-Delphi process, participants rated the seriousness of health outcomes (round 1), reviewed and discussed the initial results (round 2), and revised their original ratings (round 3). Panelists assigned seriousness ratings (0, [not serious] to 100 [most serious]) for infant death, stillbirth, preterm birth, gestational diabetes, preeclampsia, small for gestational age (SGA) birth, large for gestational age (LGA) birth, unplanned cesarean delivery, maternal obesity, childhood obesity, and maternal metabolic syndrome. RESULTS: Each panel individually came to a consensus on all seriousness ratings. The final median seriousness ratings combined across all panels were highest for infant death (100), stillbirth (95), preterm birth (80), and preeclampsia (80). Obesity in children, metabolic syndrome in women, obesity in women, and gestational diabetes had median seriousness ratings ranging from 55 to 65. The lowest seriousness ratings were for SGA birth, LGA birth, and unplanned cesarean delivery (30 to 40). CONCLUSION: Professionals and women rate some adverse outcomes as being more serious than others. These ratings can be used to establish the range of pregnancy weight gain associated with the lowest risk of a broad range of maternal and child health outcomes.